2021
DOI: 10.3390/cancers13246250
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial High-Dose-Rate Brachytherapy of Liver Metastases in Oligometastatic Patients

Abstract: Local ablative treatments have emerged as a promising treatment strategy for patients with oligometastatic disease. Among others, interstitial brachytherapy (iBT) is an upcoming treatment option for unresectable liver metastases. We report the feasibility and oncologic outcome of iBT of oligometastatic liver metastases performed in patients with limited tumor burdens in a high-volume center. Patients undergoing iBT between August 2017and March 2019 were included. A retrospective analysis of patient outcomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Local ablative treatment techniques have emerged as promising strategies for HCC. iBT has been shown to be a safe and effective treatment option for liver lesions in early-stage HCC [ 23 , 24 ]. Patients referred to iBT usually are present with larger lesions or those not suitable to surgical resection or other local treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Local ablative treatment techniques have emerged as promising strategies for HCC. iBT has been shown to be a safe and effective treatment option for liver lesions in early-stage HCC [ 23 , 24 ]. Patients referred to iBT usually are present with larger lesions or those not suitable to surgical resection or other local treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its toxicity and the development of platinum-based chemotherapeutic agents, whole abdominal radiation is soon no longer routinely used in the clinical management of ovarian cancer and only used for the treatment of isolated lesions ( 26 , 27 ). Interstitial brachytherapy, a form of radiotherapy, has achieved excellent success treating a variety of solid cancers ( 28 , 29 ). Because the recurrent lesion is solitary in our patient, interstitial brachytherapy can provide a greater dosage to control the tumor and achieve good therapeutic benefits of CR without having the negative side effects of traditional radiotherapy, which is essential for improving the patient’s PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to compare the safety and efficacy of brachytherapy to local ablative EBRT and systemic therapies in patients with non-resectable HCC and intrahepatic cholangiocarcinoma [ 48 ]. Although SIRT remains a primary area of research for liver malignancy indications, evaluations of HDR brachytherapy have previously been reported to be an effective treatment of liver metastases with good local control and low toxicity [ 49 , 50 ]. Long-term follow-up studies of LDR (n = 64) and HDR (n = 75) [ 51 ] brachytherapy to treat liver malignancies concluded that brachytherapy is an effective treatment option for unresectable primary and metastatic tumors, with one year LDR local control rates of 44% and HDR local control rates of 48–94% based on tumor size.…”
Section: Gastrointestinalmentioning
confidence: 99%